Altered expression of interleukin-6, interleukin-8 and their receptors in decidua of women with sporadic miscarriage - Pitman, Hedele; Innes, Barbara A; Robson, Stephen C; Bulmer, Judith N; Lash, Gendie E (Human reproduction (Oxford), 2013)
Are alterations in decidual expression of interleukin (IL)-6 and IL-8 associated with sporadic miscarriage? IL-6 and IL-8 secretion from decidual uterine natural killer (uNK) cells and macrophages isolated from women with spontaneous miscarriage was reduced compared with normal controls. Miscarriage is a common gynaecological problem with huge financial and personal implications. Eleven to twenty per cent of all clinically recognized pregnancies are lost before the 20th week of gestation, with miscarriages often being divided into early (≤ 12 completed weeks from last menstrual period) and late (≥ 13 weeks). Spiral artery remodelling is a key feature of early pregnancy; failure of this process has been implicated in sporadic miscarriage. The molecular triggers that initiate spiral artery remodelling are not clear, although cytokines such as IL-6 and IL-8 may play a role. This was a laboratory-based study using decidual and placental bed biopsy samples from women with sporadic miscarriage (n = 30) and termination of pregnancy controls (n = 30). Total adherent decidual cells, CD10(+) stromal cells, CD14(+) macrophages and CD56(+) uNK cells were isolated from decidua from apparently normal pregnancies that were terminated at either 8-10 or 12-14 weeks' gestation. In addition, CD14(+) macrophages and CD56(+) uNK cells were isolated from decidua from sporadic miscarriage at 8-10 weeks' gestation. Secreted IL-8 was measured in all isolated cell populations, while IL-6 was measured in CD14(+) macrophages and CD56(+) uNK cells from both sporadic miscarriage and normal controls. Placental bed biopsies were taken from women after sporadic miscarriage or termination of pregnancy at ≤ 12 completed weeks' or >13 weeks' gestational age, formalin-fixed, paraffin-embedded and immunostained for IL-6, IL-6Rα, GP130, IL-8, CXCR1, CXCR2 and CD13 (aminopeptidase N). Staining intensity for each factor was assessed in extravillous trophoblast cell populations, myometrial and decidual stroma, myometrial and decidual spiral arteries and decidual glandular epithelium. A CPA model was used to assess the potential role of IL-6 and IL-8 in spiral artery remodelling. IL-8 was secreted by total adherent decidual cells, CD10(+) stromal cells and CD14(+) macrophages at both 8-10 and 12-14 weeks' gestation, with CD14(+) cells secreting the highest levels. Both CD14(+) and CD56(+) cells isolated from decidua of early sporadic miscarriage produced lower IL-6 (P = 0.04, P = 0.01, respectively) and IL-8 levels (P = 0.0007, P = 0.002, respectively) compared with normal cases. In addition, altered expression of IL-6, IL-8 and their receptors was observed in various cell types in placental bed (myometrial stroma, glandular epithelium, interstitial extravillous trophoblast cells, vascular smooth muscle cells and endothelial cells) in sporadic miscarriage, particularly from later gestational ages. IL-6 and IL-8 disrupted vascular smooth muscle morphology and organization in an in vitro model of spiral artery remodelling. By the nature of sampling at the time of miscarriage, it was not possible to ascertain the cause or effect in the observed alterations of levels of IL-6 and IL-8 in sporadic miscarriage. Alterations in the expression of IL-6, IL-8 and their receptors may be associated with the aetiology of sporadic miscarriage, especially given the potential role of these cytokines in the regulation of trophoblast invasion and spiral artery remodelling. This project was supported by funding from Wellbeing of Women (RG1000). The authors have no competing interests to declare. Not applicable.